HARMONISASI PENGUKURAN KINERJA BANK SYARIAH: MAQASID SHARIAH INDEX DAN RASIO KEUANGAN - Husni Shabri; Ahmad Rodoni (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
This paper aims to analyze the performance of Islamic Rural Banks in West Sumatra Province. This paper uses the quantitative method. The population of this research was all Islamic Rural Banks in West Sumatra Province of seven banks.  The paper uses The seven Islamic Rural Banks annual reports within 2018-2020 from website Otoritas Jasa Keuangan (OJK). The analysis uses the Integrated Maqashid al-Shariah based Performance Measure (IMSPM). The results showed that the performance of the Islamic Rural Banks in the Maqashid Syariah Index with the highest achievement on the object of faith (din) for a period of three years. The study found that there were no activities for the Islamic Rural Banks on the object of  intellect ('aql) and on the object of posterity (nasl).The results of performance measurement with the IMSPM model can be a notification for Islamic Rural Banks in West Sumatra regarding more efforts to realize maqashid shariah in the Islamic banking industry.